Understanding Justice: Criminal Courtroom Interpretation in Eighteenth-Century London and Twenty-First-Century Toronto - Macfarlane, Karen (TTR, 2007)
AbstractThis paper compares criminal courtroom interpretation in present-day Toronto with eighteenth-century London. Eighteenth-century London, like Toronto, was home to a large immigrant population, and faced similar challenges. This article argues that expedience was the most important factor in shaping eighteenth-century criminal courtroom interpretation. The right to an interpreter is now a constitutional and common law right. Modern defendants enjoy greater protections, such as the developments of the presumption of innocence, the law of evidence, and the right to legal counsel. However, the attitudes of many Anglophone trial participants remain unchanged and negatively affect defendants who use interpreters.